Learning Design on Social Studies Through Digital Book in Senior High School - Budiaman, Budiaman; Komarudin, Komarudin; Nuruddin, Nuruddin; Kustandi, Cecep (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The diversity of Indonesian society, from ethnicity, religion, race, and class, is a social asset that harmony must be maintained. Multicultural education has an important role in maintaining this harmony. Prospective social science education teachers must have an attractive learning design in increasing understanding related to multicultural education. This study aims to see the effect of digital book learning design on multicultural education for prospective teachers. Researchers collaborated with students of the 2017 social science education study program, faculty of social science, Jakarta State University. Analysis of learning outcomes with two-way MANCOVA analysis with one covariate. The results show the interest in learning multicultural education, a significance value of 0.955 which is greater than 0.05, then H0 is accepted. The significance value obtained from all outputs is 0.000 which is smaller than 0.05, so H0 is rejected. So, it can be concluded that there is an effect of using digital book learning media on students’ multicultural education